2015
DOI: 10.1073/pnas.1515978112
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of RNA-DNA differences underlies interindividual variation in the human IL12RB1 mRNA repertoire

Abstract: Human interleukin 12 and interleukin 23 (IL12/23) influence susceptibility or resistance to multiple diseases. However, the reasons underlying individual differences in IL12/23 sensitivity remain poorly understood. Here we report that in human peripheral blood mononuclear cells (PBMCs) and inflamed lungs, the majority of interleukin-12 receptor β1 (IL12RB1) mRNAs contain a number of RNA-DNA differences (RDDs) that concentrate in sequences essential to IL12Rβ1's binding of IL12p40, the protein subunit common to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…However, with the advent of the Human Genome Project and the discovery of noncoding RNAs, this simplistic concept has been repeatedly challenged. DNA-RNA discrepancies have been previously reported: peripheral blood mononuclear cells (Ju et al 2011), immortalized B cells (Peng et al 2012), at the interleukin-12 receptor β1 (IL-12Rβ1) locus in peripheral blood mononuclear cells (Turner et al 2015), and at three specific loci in the human mitochondrial DNA from different cell types (Bar-Yaacov et al 2013). Notably, these DNA-RNA discrepancies have only been reported in normal tissues and their incidence in human diseases is still unknown.…”
Section: Ccat2 Induces Myeloid Malignanciesmentioning
confidence: 99%
“…However, with the advent of the Human Genome Project and the discovery of noncoding RNAs, this simplistic concept has been repeatedly challenged. DNA-RNA discrepancies have been previously reported: peripheral blood mononuclear cells (Ju et al 2011), immortalized B cells (Peng et al 2012), at the interleukin-12 receptor β1 (IL-12Rβ1) locus in peripheral blood mononuclear cells (Turner et al 2015), and at three specific loci in the human mitochondrial DNA from different cell types (Bar-Yaacov et al 2013). Notably, these DNA-RNA discrepancies have only been reported in normal tissues and their incidence in human diseases is still unknown.…”
Section: Ccat2 Induces Myeloid Malignanciesmentioning
confidence: 99%
“…To determine if IL12RB1 expression in the lungs is allele biased, we deep sequenced IL12RB1 gDNA and mRNA from human lung specimens, determined each donor genotype at eleven polymorphic positions in the IL12RB1 gene, and then used this information to educe the allelic origin of IL12RB1 mRNA in the same specimen. Deep sequencing was done using the Ion Torrent platform as previously described 43 ; the average IL12RB1 gDNA and mRNA read depths across all samples were 2907× and 13222×, respectively ( supplemental TABLE S2 ). To determine a donor’s genotype, we queried their gDNA sequence at eleven polymorphic sites in the IL12RB1 gene (chromosome 19 positions 18170384, 18170755, 18180413, 18180451, 18186575, 18186618, 18188408, 18191664, 18192977, 18194255 and 18197635), and whether they were heterozygous (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA (gDNA) and messenger RNA (mRNA) were extracted from human tissues and cell lines using the AllPrep DNA/RNA method (Qiagen, Germantown, MD). We performed PCR amplification and Ion Torrent sequencing of IL12RB1 gDNA/mRNA per our previously reported methods 43 . Single nucleotide polymorphisms (SNPs) in the donor IL12RB1 gDNA sequence were identified by comparing the donor gDNA sequence to the reference genome build Hg19.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, hundreds of thousands of ADAR-mediated editing sites have been identified in human cells (Kawahara et al 2004;Ju et al 2011;Alon et al 2012;Chen et al 2012;Peng et al 2012;Silberberg et al 2012;Vesely et al 2012;Chen 2013;Wang et al 2013;Bazak et al 2014). Furthermore, we and others have found that there are other types of RNA-DNA sequence differences (RDDs) that are unlikely to be mediated by these deaminases (Li et al 2011;Bahn et al 2012;Bar-Yaacov et al 2013;Rubio et al 2013;Turner et al 2015). These events are found in normal cells, and altered patterns of RDDs were found in neurologic diseases (van Leeuwen et al 1998;Silberberg et al 2012;Krestel et al 2013;Wang et al 2014) and in cancers (Klimek-Tomczak et al 2006;Martinez et al 2008;Lee et al 2013;Avesson and Barry 2014;Han et al 2014;Niavarani et al 2015).…”
mentioning
confidence: 99%
“…The first published work we know of is a G-to-A site in WT1, Wilms tumor 1 (Sharma et al 1994). Subsequently RDD sites in brain tissues from Alzheimer's and Down syndrome patients (van Leeuwen et al 1998) and in other human cells were identified (Ju et al 2011;Bahn et al 2012;Silberberg et al 2012;Turner et al 2015;Zhang et al 2015). A recent paper suggests that APOBEC3A is the protein that mediates G-to-A RDD in WT1 (Niavarani et al 2015).…”
mentioning
confidence: 99%